PENYELENGGARAAN PEMILU SERENTAK MEMPERKUAT SISTEM PRESIDENSIAL DI INDONESIA - Parlindungan S, Gokma Toni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Simultaneous general elections are essentially aimed at forming a stable government, an effective and strong parliament, as well as the DPR's political support for the elected President, which turns out to be an important variable that cannot be ignored. Based on the provisions of the constitution which states that the authority to make laws is jointly with the President and the DPR, as well as other policies. This situation shows that, Separation of Power – where the power of one branch of government will limit the power of another – is not the basic principle of our presidential system. Rather, it is the convergence of power, where the branches of power collaborate with each other to produce a law or a policy. This condition is referred to as the phenomenon of Presidential Parliamentarization. This is so because the President, who should be strong or at least equal in position to the DPR, has become weak. So that what appears is not collaboration, but rather the domination of the DPR over the President. The experience of Latin American countries provides a very good lesson for that, so that the government runs effectively in a multi-party presidentialism country, the implementation of simultaneous national elections is used as a method. Because the effectiveness itself is used by the level of interaction and heterogeneity between the existing political forces so that it does not depend on whether or not multiple party systems are implemented, the simultaneous implementation of elections is actually intended to create consensual democracy.